Metal–Organic Framework Membranes: Advances, Fabrication, and Applications. Issue 4 (20th March 2022) - Jia, Shuyue; Ji, Dongxiao; Wang, Liming; Qin, Xiaohong; Ramakrishna, Seeram
Abstract : Metal–organic frameworks (MOFs) are emerging porous materials with the characteristics of uniform metal center distribution and adjustable pore size. They have important applications in the fields of energy, environment, and catalysis. However, the practical application of MOFs is limited due to insolubility, brittleness, and hard processing. Shaping MOFs into a useful structure is an urgent need. In this review, the research progress in the fabrication of MOF membranes is introduced with emphasis on two paths: the preparation of pure MOF membranes and the incorporation of MOFs into polymer matrix. The classic and emerging principles to prepare pure MOF membranes and MOF/polymer hybrid membranes are summarized. Through the analysis of classic cases, the advantages and disadvantages of different preparation strategies and products are compared, to provide general knowledge for the needs of different application scenarios. Finally, the important role that the MOF membrane plays in the applications of separation, adsorption, and catalysis is highlighted. The opportunities and challenges of MOF membranes in this new era are also proposed. Abstract : This review summarizes the developments on the synthesis methods for pure metal–organic framework (MOF) membranes and MOF/polymer hybrid membranes. Their applications in the energy and environmental fields are highlighted, and the limitations and challenges of the MOF membranes are also discussed.